Modern Arabic poetry 1800-1970 : the development of its forms and themes under the influence of Western literature - Moreh, Shmuel. (Studies in Arabic literature ;, 1976)
"The purpose of this book is to trace the development of the differing forms employed in various liteary movements in modern Arabic poetry. This development seems to me the most important elemment in the understanding of the contemporary revolution in Arabic poetry. Moreover, this revolution is considered to be the first in the history of Arabic poetry in which the influence of foreign literature has been such that it las almost completely cut off modervn Arabic poetry from its classical heritage." from Introduction.